2017
DOI: 10.1039/c7dt00134g
|View full text |Cite
|
Sign up to set email alerts
|

Iodide and triiodide anion complexes involving anion–π interactions with a tetrazine-based receptor

Abstract: Protonated forms of the tetrazine ligand L2 (3,6-bis(morpholin-4-ylethyl)-1,2,4,5-tetrazine) interact with iodide in aqueous solution forming relatively stable complexes (ΔG° = -11.6(4) kJ mol for HL2 + I = (HL2)I and ΔG° = -13.4(2) kJ mol for HL2 + I = [(HL2)I]). When solutions of [(HL2)I] are left in contact with air, crystals of the oxidation product (HL2)(I)I·4HO are formed. Unfortunately, the low solubility of I complexes prevents the determination of their stability constants. The crystal structures of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 111 publications
5
73
0
1
Order By: Relevance
“…The fabrication of cheap and large‐area PSCs in also fundamental for the design of energy conversion/storage integrated devices, especially when PSCs should recharge batteries or supercapacitors . More broadly, photovoltaics is the ideal interface for many current technologies …”
Section: Beyond Spin‐coating Processes: Towards Large‐area Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication of cheap and large‐area PSCs in also fundamental for the design of energy conversion/storage integrated devices, especially when PSCs should recharge batteries or supercapacitors . More broadly, photovoltaics is the ideal interface for many current technologies …”
Section: Beyond Spin‐coating Processes: Towards Large‐area Pscsmentioning
confidence: 99%
“…[148][149][150][151] More broadly,p hotovoltaics is the ideal interface for many current technologies. [152][153][154][155][156][157][158][159][160][161]…”
Section: Beyond Spin-coating Processes:t Owards Large-area Pscsmentioning
confidence: 99%
“…8 A close contact with an anion or a lone electron pair is possible for electron-depleted rings and a number of such interactions have been documented. [9][10][11][12][13][14][15][16] Unlike aromatics, which are mostly electron-rich (except those with five or six electronwithdrawing substituents), quinoid rings are inherently electron-poor due to a lack of electron delocalization and the presence of carbonyl groups; they can be further depleted by introduction of electronegative substituents. Perhalogenoquinones act as mild oxidants and can easily be reduced into semiquinone radicals by mild reducing agents such as iodide ions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polyiodide systems have recently encountered a broad technological interest, mainly connected with solar energy harvesting and storage, e.g., dye-sensitized solar cells and batteries, where they have been successfully implemented as electrolyte in various forms [12,13]. Solid-state conductors based on the Grotthus conduction mechanism [3,14] are also a major field of research [15][16][17]; on this side some of us recently reported about the possibility of using supramolecular forces, such as the strong anion-π interactions exerted by s-tetrazines [18], to direct the assembly of polyiodide networks [19].…”
Section: Introductionmentioning
confidence: 99%